اختلاف آراء الفقهاء حول تطبيق منتجات التورق المنظم و بيع العينة و الدين في المصارف الإسلامية - محمود، محمود بن محمد علي (الجامعة الإسلامية العالمية, 2012)
تهدف هذه الدراسة إلى بيان الطريقة التي تطبق بها منتجات المصارف الإسلامية الماليزية، ومعالجة تلك التطبيقات التي أدت إلى الخلاف بين فقهاء ماليزيا والمشرق الإسلامي. ووضحت الدراسة محل الاختلافات الفقهية مبينة أن ما يثار من مثل هذه الخلافات يتركز في طريقة تطبيق بعض صور المسائل الاجتهادية التي أخذت بها الهيئات الشرعية في ماليزيا، وهذه الأساليب في طريقها للترشيد إلى الثواب. وقد اعتمد الباحث على المنهجين الأساسيين وهما: المنهج التحليلي النقدي، والمنهج المقارن بغية الوصول إلى النتائج المرجوة. وأخيرا، قد تحفظ الباحث على طريقة بعض الأساليب التي تطبق بها منتجات المعاملات المالية، موضحة آراء الفقهاء المعاصرين، وحكم الشرع فيها، مما يلزم النظر فيها ومراجعة تطبيقها لتنضبط بالضوابط الشرعية. This study aims to describe how Malaysian Islamic banking products are implemented and how some of these implementations lead to disagreement between the Islamic jurists of Malaysia and Islamic East. The study pointed out the areas of juristic differences indicating that these differences are rooted in the process of applying some forms of ijtihadli issues that are accepted by the Malaysian religious bodies and these methods are in the process of improvement towards accuracy. The researcher maintained reservation on some methods applied in the products of financial transactions; in doing so, the researcher explained the relevant views of contemporary jurists and Shari'ah rulings that require re-consideration and review of their applications in order to modulate them with Shari'ah regulations. The researcher has relied on two primary approaches: critical cum analytical and comparative.
Keywords: الفقهاء -- الفقه الإسلامي -- فقه المعاملات -- البنوك الإسلامية -- التورق -- البيوع -- ماليزيا